The Differences of Body Image, Energy Intake Level, and Nutritional Status Between Health and Non Health Female Student of Jenderal Soedirman University - Mulyani, Sri (Jurnal Gizi dan Pangan Soedirman, 2018)
This study aims to knowing the differences in body image, level of energy intake, and nutritional status in female students of accounting and nutrition science at Jenderal Soedirman University. This study uses a cross-sectional study conducted on 96 female students of accounting and nutrition science with purposive sampling technique. Body image is measured with a Body Shape Questionnaire (BSQ-16B). The level of energy intake is obtained through a 24-hour non-consecutive recall. Nutritional status is measured using a body mass index (BMI). Most accounting students have a negative body image (52.1%), less energy intake (43.8%) and normal nutritional status (79.2%). Most of the nutrition students have a positive body image (56.2%), less energy intake level (45.8%), and normal nutritional status (70.8%). Based on the analysis using the Mann Whitney test, there was no difference in body image and level of energy intake between accounting and nutrition science students. There are differences in nutritional status between accounting and nutrition science students.